Some results on symmetric duality of multiobjective programmes with generalized (F,ρ) invexity - Ojha D.B.; Mukherjee R.N. (My University, 2025)
In this present article we have given some multiobjective programming problems with their symmetric duals and have derived weak and strong duality results with respect to such programs. Moreover, we have also used most general type of invexity assumptions involved with the functions which are related to the programming problems. It is to be pointed out that the objective functions in such programs contain terms like support functions which in turn are able to give results on particular classes of programs involving quadratic terms. Our results in particular give as special cases some earlier results on symmetric duals given in the current literature. © 2004 Published by Elsevier B.V.